Significance of Nitrogen Limited Medium (NLM) Components on Lipid Production Lipomyces starkeyi Y853 - Khairani, Aqila Raihana; Ilmi, Miftahul (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Oleaginous yeasts, such as Lipomyces starkeyi, can convert carbon and nitrogen sources into lipids up to 50% of the cell's dry weight. A high lipid percentage was achieved (53.5%) using Nitrogen Limited Medium (NLM), which indicates that the components of NLM play a role in the production of biomass and lipids. Nevertheless, the statistical analysis of the role of NLM components on lipid production has not yet been conducted. Thus, this research was designed and carried out to determine the role of NLM components in lipid production using Plackett-Burman Design. The results show that the variables had an insignificant impact on lipid production based on the ANOVA test (P >0.05). Additionally, main effect plots were generated to identify the negative and positive effects of the components. The graph indicates that peptone and yeast extract (YE) are essential components in high concentrations to increase lipid production. This result was due to the insufficient concentration used in this experiment (YE= 0.5 g/L; peptone= 0.3 g/L) compared to the optimal conditions (YE= 8 g/L; peptone= 3 g/L). Therefore, further research should be conducted with the addition of external factors (pH, temperature, shaker speed) to acquire more significant results on biomass lipid production.